Watering country: Aboriginal partnerships with environmental water managers of the Murray–Darling Basin, Australia. Issue 3 (3rd July 2019) - Jackson, Sue; Nias, Deb
ABSTRACT: A complex environmental water governance system has developed in Australia over the past decade, with institutional arrangements that allow government and non-government organisations to acquire and manage substantial volumes of water for the benefit of the environment. Management of environmental water in partnership with other parties presents Aboriginal people with an opportunity to access water and restore environments, as well as reaffirm and rebuild socio-ecological relationships and water-dependent livelihoods. This article describes the emergence of collaborative partnerships between environmental water managers and Aboriginal community organisations in the Murray–Darling Basin to water country. Through case study profiles, the article shows how Aboriginal organisations and water managers are working together to improve the quality of wetlands, as perceived by traditional owners and others, and to share more equitably in the benefits from the acquisition and management of environmental water. The constraints and barriers are discussed, alongside the conditions that have laid the foundations for this emerging form of co-management of water.